MEASURING REGIONAL PUBLIC HOSPITAL (RSUD) DAYA MAKASSAR PERFORMANCE WITH CONTEMPORARY MANAGEMENT ACCOUNTING APPROACH - Nur Rahmah Usman; Syamsu Alam; Asriani Junaid (Universitas Islam Balitar, 2017)
This research aims to look at how the mechanism of performance evaluation and measurement using contemporary management accounting methods to provide comprehensive and long-term insightful performance information and identify critical success factors. This research uses primary and secondary data through questionnaires, interviews and written data documentation. Data analysis method used is strategy mapping approach using the Balanced Scorecard. The results showed that the performance of Daya Makassar Hospital was stated to be good. It refers to the four perspectives of the assessed Balanced Scorecard. From the customer's perspective, it can be stated as good at the level of satisfaction of patients who are satisfied. From an internal business perspective it is also said to be good by looking at each of the overall assessment indicators as well. In the perspective of growth and development is also expressed well by looking at indicators that meet the standard. From a financial perspective it is declared good because it has reached a level of efficiency.